Walking coral: Complex phototactic mobility in the free-living coral Cycloseris cyclolites. - Brett M Lewis; David J Suggett; Peter J Prentis; Luke D Nothdurft (PLoS ONE)
Not all corals are attached to the substrate; some taxa are solitary and free-living, allowing them to migrate into preferred habitats. However, the lifestyle of these mobile corals, including how they move and navigate for migration, remains largely obscure. This study investigates the specific biomechanics of Cycloseris cyclolites, a free-living coral species, during phototactic behaviour in response to blue and white light stimuli. Our results indicate a strong positive phototactic response to blue light with 86.7% (n = 15) of samples moving towards the light source, while only 20% (n = 15) samples responded similarly to white light (400-700 nm). Locomotion, characterised by periodic pulses lasting 1-2 hours, involved distances up to 220 mm in blue light trials, whereas significantly shorter distances were observed in white light trials (2, 5 and 8 mm). Trails with two light sources reinforced the preference for blue light over white, with all samples consistently moving towards the blue light and away from the white (11, 15 and 3mm). High-resolution time-laps captured the biomechanics of forward motion that appeared driven by three key factors: tissue inflation, which increased contact surface area for lift and friction; the ventral foot/pads, adjusting substrate interaction/friction; and the contraction and twisting of lateral peripheral tissues, which propelled the coral forward in a coordinated manner resembling the pulsed swimming motion of jellyfish. Our findings provide new insights into coral mobility mechanisms, emphasising the role of tissue inflation in active locomotion, with potential implications for coral neural systems, vision and habitat selection.